Analisis sektor unggulan dan perubahan struktur ekonomi pada Provinsi Kepulauan Bangka Belitung sebagai provinsi hasil pemekaran - Alviansyah, Vito Jorghi; Nurhayati, Siti Fatimah (Nur Science Institute, 2024)
The research analyzes regional superior sectors and economic changes in the Bangka Belitung Islands Province due to the expansion. Esteban Marquillas' Shift Share analysis was used in research using secondary data from the Central Statistics Agency in the Bangka Belitung Islands Province. This research analysis shows that the processing industry, forestry, and fisheries sectors are the regional primary sectors among the 17 business sectors in the Bangka Belitung Islands Province. Then, changes in the economic structure throughout 2020–2022 are said to be a transition period. Therefore, most local people are still involved in the secondary and primary sectors, compared to the tertiary and service sectors.